Wer wird gefördert? Die Konstruktion von Stipendienwürdigkeit durch Lehrer:innen - Proskawetz, Franziska Sophie (Verlag Barbara Budrich, 2024)
Social background determines educational success in Germany. The unequal distribution of educational opportunities is also evident in the area of support for the gifted: although giftedness and intelligence are normally distributed in society, students from less privileged backgrounds are underrepresented in scholarship programmes and support for the gifted. The reasons can be found among teachers who nominate students for support programmes. The study uses the RuhrTalente scholarship programme to analyse how teachers construct scholarship eligibility. From the results, measures can be derived that can contribute to a long-term reduction of educational injustice.